PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN SEKTOR ENERGI SUB SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2023-2025 - Sitti Muliana; Hasriana Hasriana; Nurlaila Hasmi; Nur Aisyah; Suriani Suriani (Jurnal Akuntansi Kompetif, 2026)
The purpose of this scientific study is to determine how profitability and leverage influence CSR disclosure. This research was conducted on companies operating in the energy sector, specifically the coal subsector, listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 46 samples were selected using a purposive sampling method. The data type used in this study is quantitative. Secondary data sources include financial statements, sustainability reports, and annual reports from these companies. In this study, the analytical method used was multiple linear regression. The findings of this study indicate that CSR is positively influenced by profitability, while leverage negatively contributes to CSR disclosure.